The Sacramental Structure of Baptism according to Tertullian - Vicastillo, Salvador (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
Tertullian defends water value, a basic element of baptism. Over the water descends, in virtue of epiclesis, the Holy Ghost. Catechumen brings into it faith, which becomes dressed and sealed by baptism.
Keywords: Tertullian; baptism; Holy Spirit